The Cerebello-Hypothalamic and Hypothalamo-Cerebellar Pathways via Superior and Middle Cerebellar Peduncle in the Rat - (:unkn) unknown (SPRINGER, 2018)
The connections between the cerebellum and the hypothalamus have been well documented. However, the specific cerebellar peduncle through which the hypothalamo-cerebellar and cerebello-hypothalamic connections pass has not been demonstrated. The present study aims to define the specific cerebellar peduncle through which connects the cerebellum to specific hypothalamic nuclei. Seventeen male albino rats received 20-50-nl pressure injections of either Fluoro-Gold (FG) or biotinylated dextran amine (BDA) tracer into the superior (SCP), middle (MCP), and inferior (ICP) cerebellar peduncle. Following 7-10days of survival period, the animals were processed according to the appropriate protocol for the two tracers used. Labeled cells and axons were documented using light or fluorescence microscopy. The present study showed connections between the hypothalamus and the cerebellum via both the SCP and the MCP but not the ICP. The hypothalamo-cerebellar connections via the SCP were from the lateral, dorsomedial, paraventricular, and posterior hypothalamic nuclei, and cerebello-hypothalamic connections were to the preoptic and lateral hypothalamic nuclei. The hypothalamo-cerebellar connections via the MCP were from the lateral, dorsomedial, ventromedial, and mammillary hypothalamic nuclei; and cerebello-hypothalamic connections were to the posterior, arcuate, and ventromedial hypothalamic nuclei. The hypothlamo-cerebellar connections were denser compared to the cerebello-hypothlamic connections via both the SCP and the MCP. The connection between the cerebellum and the hypothalamus was more prominent via the SCP than MCP. Both the hypothlamo-cerebellar and cerebello-hypothalamic connections were bilateral, with ipsilateral preponderance. Reciprocal connections were with the lateral hypothalamic nucleus via the SCP and the ventromedial nucleus via the MCP were observed. Cerebellum takes part in the higher order brain functions via its extensive connections. The knowledge of hypothalamo-cerebellar and cerebello-hypothalamic connections conveyed within the SCP and MCP can be important for the lesions involving the MCP and SCP. These connections can also change the conceptual architecture of the cerebellar circuitry and deepen current understanding.
Keywords: Hypothalamus; Cerebellar; Connections; Superior; Middle; Cerebellar peduncle; PROGRESSIVE SUPRANUCLEAR PALSY; JOUBERT-SYNDROME; FASTIGIAL NUCLEUS; IMMUNE FUNCTION; PROJECTION; CAT; CONNECTIONS; ACTIVATION; CIRCUITS; LESIONS